2017
DOI: 10.1111/jocd.12341
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet‐rich plasma versus readymade growth factors in skin rejuvenation: A split face study

Abstract: Platelet-rich plasma is effective and safe for skin rejuvenation, comparable to readymade growth factors with noticeable higher longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 26 publications
2
32
0
1
Order By: Relevance
“…This study exhibited more promising results with the combined therapy of dermaroller and PRP for volunteers with photoaging when compared to the other side treated only with dermaroller ( P = 0.039), or combined with TCA ( P = 0.048). This is in agreement with Gawdat et al . who suggested the use of PRP for skin rejuvenation as an effective and safe tool for correction of aging signs, owing to the significantly higher patient satisfaction, fewer side effects, and more sustainable results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study exhibited more promising results with the combined therapy of dermaroller and PRP for volunteers with photoaging when compared to the other side treated only with dermaroller ( P = 0.039), or combined with TCA ( P = 0.048). This is in agreement with Gawdat et al . who suggested the use of PRP for skin rejuvenation as an effective and safe tool for correction of aging signs, owing to the significantly higher patient satisfaction, fewer side effects, and more sustainable results.…”
Section: Discussionsupporting
confidence: 91%
“…Autologous PRP creates an instant, long‐lasting volumetric effect with natural looking results and optimal patient satisfaction . It's efficient and safe for skin rejuvenation when compared with ready‐made growth factors …”
Section: Discussionmentioning
confidence: 99%
“…A split‐face trial with 20 Asian females showed that PRP treatment is an effective alternative treatment method for infraorbital skin rejuvenation compared with PPP and normal saline, more safely and more easily applied . And in contrast to the readymade growth factors, autologous PRP also appeared to be safer and more effective for skin rejuvenation . And there are several pointed trials in various aspects of facial rejuvenation.…”
Section: Application Of Prpmentioning
confidence: 61%
“…PRF has been widely used in clinical practice to improve the efficacy of cell-assisted lipotransfer (CAL) and wound repair by ASCs, due to its advantages in preventing immunologic rejection, simple production, and few complications. Moreover, plastic surgeons have adopted PRP, a predecessor of PRF, as a rejuvenator to treat aging skin by intradermal injection [8, 34, 35]. …”
Section: Discussionmentioning
confidence: 99%